Prevalence of Patients with Oral Cavity Tumours at Hospital Abdoel Wahab Sjahranie Samarinda 2016-2020 - Rienda 'Afifah Khairunnnisa; Sinar Yani; Cristiani Nadya Pramasari (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: Tumour is an uncontrolled swelling of tissue. Tumour caused by uncontrolled proliferation abnormal tissue and cell. Based on the nature of the tumour, there are two types of tumours, that is benign tumour and malignant tumour. The malignant tumour can cause death while benign tumour only aggravate the surrounding tissue.The high incidence of tumors in various countries, including Indonesia, rarely finds research on the prevalence of oral tumors, especially in East Kalimantan, especially the capital city of Samarinda. Objective: This research is to find out the incidence of oral cavity tumour at RSUD Abdoel Wahab Sjahranie periode 2016-2020 . Method: Used was a descriptive observational method retrieving secondary data in the form of medical records. The sampling method used in this research was the purposive sampling method. Results: the profile of patients with oral cavity tumour at Regional General Hospital Abdoel Wahab Sjahranie 2016-2020 are as follows the age group with the highest incidence is 46-55 years: 32 patients (24,8%), The highest incidence by gender were women: 78 patients (60.5%) and man: 51 patients (39,5%). Most of the tumour were found in the mandible: 65 patients (50,4%). Conclusion: The prevalence of oral cavity tumour is higher in female patients than male patients.